Effects of dietary glyceryl monolaurate supplementation on growth performance, non-specific immunity, antioxidant status and intestinal microflora of Chinese mitten crabs. Issue 125 (June 2022) - Fu, Chunsheng; Cui, Zhenchuan; Shi, Xueyan; Liu, Jinsong; Jiang, Ying; Zhang, Ruiqiang
Abstract: This study aims to investigate the effects of glycerol monolaurate (GML) on growth performance, non-specific immunity, antioxidant capacity and intestinal microflora in Chinese mitten crabs. The crabs were randomly arranged to three experimental diets groups containing 0 (control group), 1000 mg/kg GML (GML1000 group), and 2000 mg/kg GML (GML2000 group), respectively. After 8 weeks of breeding, results showed a better growth performance in GML2000 group, with a higher PWG, SGR and lower FCR ( P  < 0.05). Meanwhile, in GML2000 group the activities of phenoloxidase, alkaline phosphatase, acid phosphatase and lysozyme in hemolymph were increased ( P  < 0.05), also the activities of hemolymph and hepatopancreas superoxide dismutase (SOD) and glutathione peroxidase (GPx) were increased in hepatopancreas ( P  < 0.05). While malondialdehyde (MDA) concentrations were lower significantly ( P  < 0.05) both in GML1000 and GML2000 groups. Furthermore, the mRNA expression of TLR1, TLR2, which related to the Toll pathway were increased ( P  < 0.05). Supplementation of 2000 mg/kg GML up-regulated the expression of ALF and LZM ( P  < 0.05), and down-regulated the expression of caspase-3 ( P  < 0.05). The abundance of Firmicutes increased in GML2000 group ( P  < 0.05), and Shewanella was significantly increased ( P  < 0.05) in both GML1000 and GML2000 groups. In conclusion, dietary supplemented with GML enhanced the growth performance and antioxidant capacity, enhanced hemolymph immune enzymes activities and antimicrobial peptides expression through regulating the proPO system and Toll pathway, and improved gut microflora in Chinese mitten crabs. Highlights: The first study of improving effects of glyceryl monolaurate (GML) in crabs. GML improved growth and hemolymph immune enzymes activities in crabs. GML increased antioxidant capacity of Chinese mitten crabs. GML enhanced immunity by regulating proPO system and Toll pathway in crabs. GML ameliorated the gut microflora in Chinese mitten crabs.